Reforma a vapor catalítica do metano: Otimização da produção e seletividade em hidrogênio por absorção in situ do CO2 produzido - Cesário, Moises Rômolos (2013)
Topics of research related to energy and environment have significantly grown in recent years, with the need of its own energy as hydrogen. More particularly, numerous researches have been focused on hydrogen as energy vector. The main portion of hydrogen is presently obtained by reforming of methane or light hydrocarbons (steam, oxy, dry or auto reforming). During the methane steam reforming process the formation of CO2 undesirable (the main contributor to the greenhouse effect) is observed. Thus, an oxide material (sorbent) can be used to capture the CO2 generated during the process and simultaneously shifting the equilibrium of water gas shift towards thermodynamically more favorable production of pure hydrogen. The aim of this study is to develop a material with dual function (catalyst/sorbent) in the reaction of steam reforming of methane. CaO is well known as CO2 sorbent due to its high efficiency in reactions of carbonation and easy regeneration through calcination. However the kinetic of carbonation decreases quickly with time and carbonation/calcination cycles. A calcium aluminate (Ca12Al14O33) should be used to avoid sintering and increase the stability of CaO sorbents for several cycles. Nickel, the industrial catalyst choice for steam reforming has been added to the support from different manners. These bi-functional materials (sorbent/catalyst) in different molar ratios CaO.Ca12Al14O33 (48:52, 65:35, 75:25, 90:10) were prepared by different synthesis methodologies, among them, especially the method of microwave assisted self-combustion. Synthesis, structure and catalytic performances of Ni- CaO.Ca12Al14O33 synthesized by the novel method (microwave assisted selfcombustion) proposed in this work has not being reported yet in literature. The results indicate that CO2 capture time depends both on the CaO excess and on operating conditions (eg., temperature and H2O/CH4 ratio). To be efficient for CO2 sorption, temperature of steam reforming needs to be lower than 700 °C. An optimized percentage corresponding to 75% of CaO and a ratio H2O/CH4 = 1 provides the most promising results since a smaller amount of water avoids competition between water and CO2 to form carbonate and hydroxide. If this competition is most effective (H2O/CH4 = 3) and would have a smaller amount of CaO available for absorption possibly due to the formation of Ca(OH)2. Therefore, the capture time was higher (16h) for the ratio H2O/CH4 = 1 than H2O/CH4 = 3 (7h) using as catalyst one prepared by impregnating the support obtained by microwave assisted self-combustion. Therefore, it was demonstrated that, with these catalysts, the CO2 sorption on CaO modifies the balance of the water gas-shift reaction. Consequently, steam reforming of CH4 is optimized, producing pure H2, complete conversion of methane and negligible concentration of CO2 and CO during the time of capture even at low temperature (650 °C). This validates the concept of the sorption of CO2 together with methane steam reforming